Breaking the silence: unveiling the intersection of climate change and youth mental health in Indonesia - Kaligis, Fransiska; Wangge, Grace; Fernando, Gabriela; Palguna, Ida Bagus Nyoman Adi; Pramatirta, Billy; Purba, Natasha Vania Theresia (Medical Journal of Indonesia, 2023)
In Southeast Asia, home to 362.2 million adolescents, the issue of adolescent mental health is aggravated by climate change. Indonesia, with its large youth population, faces a concerning prevalence of mental health challenges, including anxiety and depression. The intersection of climate change and youth mental health is manifested in the complex interaction of environmental hazards, societal changes, and psychological impact on adolescents and young people. Climate-related hazards exacerbate the existing and give rise to new mental health issues in youths, notably anxiety and post-traumatic stress disorder, and the emerging concepts such as eco-anxiety. Eco-anxiety, a novel concept, amplifies these concerns as youths grapple with climate change-related fears despite not yet being recognized as a formal mental disorder. To address this concern, immediate action should be taken, such as advocating for increased mental health support, youth involvement in climate initiatives, youth advisory committees, increased funding for mental health interventions, and the formulation of a youth-centered mental health policy. This call to action is crucial not only for Indonesia but also provides a framework for addressing similar global challenges, empowering adolescents to confront climate-induced mental health issues while nurturing their resilience.